Illegális kivándorlás Ung vármegyében a 19–20. század fordulóján - Varga, Róbert (Hallgatói Műhelytanulmányok, 2022)
Varga, Róbert: Illegal emigration in Ung County at the turn of the 19–20th centuries The most substantial topic to deal with today is migration, and their negative effects. This can be considered the biggest issue nowadays. An issue that affects all developing countries in the 21st century and it is indeed an old problem. One of the reasons for emigration was that some people were living in bad financial situation and the number of poor people were high at that time. Whichever era/century we examine, the head of the family’s primary concern was to take care of his wife and children. Because of hopelessness and poverty, people have embarked on bolder adventures, for stories have been told that wealthy countries lie beyond the ocean. The illegal emigration was also a problem in Ung county. The cause of this emigration was poverty and the business opportunity of it was soon recognized by criminal organizations. In order to stop illegal migration, countries established agencies. There were two law enforcement organizations: The Royal Gendarmerie and the Uzhorod city police. The task of the gendarmerie was to take actions against human smuggling in the country, while their colleagues had to contend with migration in the city of Uzhorod.